Diagnostic Clues and Management of ectopic Pregnancy in Sir Salimullah Medical College and Mitford Hospital, Dhaka (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Ectopic pregnancy is a common clinical condition. Diagnosis and managementof this condition is necessary in due to day practice.Methods: A cross sectional study on ectopic pregnancy was conducted in Sir SalimullahMedical College and Mitford Hospital (SSMC & MH) , Dhaka, with the objective to analyzethe risk factors and assess the results of management with respect to maternal morbidityand mortality of ectopic pregnancy during the last two years.Result: Fifty patients were admitted with ectopic pregnancy from 1st January 2008 to 31stDecember 2010.Frequency of ectopic pregnancy were 1.5% of total 3252 pregnancies. Riskfactors were found in 45% of cases. Surgical treatment were performed in total 43 patients.There was one heterotrophic pregnancy and one case of abdominal pregnancy. Four patientswere given intramuscular Methotrexate and two un-ruptured ectopics resolved spontaneouslyafter by expectant management.Conclusion: Conservative management was an option but surgical treatment was donemore often because of late referrals. Screening of high risk cases, early diagnosis and earlyintervention would reduce the morbidity in ectopic pregnancies.Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 49-53